Engineering Perspectives: Thermal and Structural Examination of Disc Brakes for Light Vehicles - Durgaprasad Dubey; Choudhary Mohd Dawood; Sanket Gangwani; Jayesh Malkar; T.Z. Quazi (International Journal of Electrical Machine Analysis and Design, 2024)
The procedure of braking transforms the kinetic energy of a car into mechanical energy that needs to be released as heat. High temperatures may result from the frictional heat produced at the disc and pad interface during the braking phase. Frictional heat produced on the rotor surface can contribute to an excessive rise in temperature, which can have unfavorable effects including premature wear, brake fluid vaporization (BFV), thermally excited vibrations (TEV), and thermal elastic instability (TEI). In order to increase the vehicle's stability and braking effectiveness, this research will examine the use of different materials in the solid type of disc brake rotor of the car. SOLIDWORKS is used to model the disc brake rotor, allowing for cross-disciplinary engineering collaboration. With ANSYS 19.2, the thermal and structural study of the disc brake rotor is carried out to ascertain the distribution of temperatures, variations in stresses, and deformation throughout the disc brake profile. Three distinct materials for solid type disc brakes are compared, and based on the amount of Von Mises stresses, distribution of temperatures, and stretching, the optimal materials and kind of disc brake have been recommended.
Keywords: : Thermal elastic instability (TEI); brake fluid vaporization (BFV); premature wear; thermally excited vibrations (TEV)